Adjunct Methods of the Standard Diabetic Foot Ulceration Therapy - Waniczek, Dariusz (Hindawi Publishing Corporation, 2013)
The outcome of management of diabetic foot ulceration (DFU) is poor and insufficient. DFU therapy includes the standard management as debridement of the wound, revascularization procedures, off-loading of the ulcer and antibacterial actions, and supplementation of growth factors and cytokines, leading to stimulation of granulation, epidermization, and angiogenesis. The aim of the present review is to summarize the adjunct methods of the standard DFU therapy as hyperbaric oxygen therapy (HBOT), maggot therapy (MT), and platelet-rich plasma therapy (PRPT). The results of preclinical and clinical trials indicated that the methods may reduce time of therapy, short-term morbidity, and the risk of major amputation.